HTLV, a multi organ oncovirus. (August 2022) - Ramezani, Samaneh; Rezaee, Seyed Abdolrahim; Farjami, Zahra; Ebrahimi, Neshat; Abdullabass, Hasaneen Kudhair; Ibrahim Jebur, Mohammad Ismael; Rafatpanah, Houshang; Akbarin, Mohammad Mehdi
Abstract: Human T lymphotropic virus (HTLV-I) is a retrovirus that has been recognized as a causative agent of two crucidal diseases, HTLV-I-Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP) and Adult T cell Leukemia-Lymphoma (ATLL). The virus not only induces those diseases in a small proportion of HTLV-I carriers (3–5%) but also it is associated with other diseases such as HTLV-I-Associated Arthropathy (HAAP), Cutaneous T Cell Lymphoma (CTCL), Graves' disease, uveitis, polymyositis, chronic respiratory diseases, lymphadenitis and dermatitis. Furthermore, HTLV related and accelerated disorders were more investigated, and the factors that might implicate in the development or progression of diseases have been discussed. We founded 13 categories of non-associated disease in studies such as Reproductive Disorders, Coronary Artery Disease (CAD), non –ATLL lymphoma, Co-infection, non-HAM/TSP neurological associated disease, non ATLL cutaneous associated disease, Autoimmune-Inflammatory related disease, Kidney disease, Liver disease, Respiratory disease, TB disease and Thyroid disease. With regard to the reviewed studies suggested HTLV-I disorders can divide into three manifests; related, accelerated and associated disease. However, interaction between HTLV-I infection and host immune response was complicated and vague. Some infectious patients indicated the involvement of inflammatory response of immune system, but in other individuals function of anti-inflammatory elements was observed. For a better understanding of this classification, more systematic studies should be designed and need to provide a global network to control and prevent HTLV affiliated diseases. Highlights: HTLV-I is a causative agent of HTLV-I-Associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP) and Adult T cell Leukemia Lymphoma (ATLL). HTLV-I/II is associated HAAP, CTCL, Graves' disease, uveitis, polymyositis, chronic respiratory diseases, lymphadenitis and dermatitis. We founded 13 categories of non-associated disease in studies. HTLV-I disorders can divide into three manifests; related, accelerated and associated disease. Interaction between HTLV-I infection and host immune response was complicated. Some infectious patients indicated the inflammatory response, but another the anti-inflammatory response is main immune events.